Estudo bibliométrico de análise de ciclo de vida aplicada a veículos automotores - Juvêncio, Jardel de Queiroz (2024)
This study presented a bibliometric analysis of articles on the Life Cycle Assessment (LCA) of motor vehicles published over the past 20 years. Bibliometric analysis, a discipline of scientometrics, uses mathematical and statistical methods to evaluate scientific publications, identifying trends and structures in specific research fields. Using data from Scopus and Web of Science, the analysis assessed the impact and trends of scientific production, correlating keywords to explore connections between themes. A total of 512 articles from the last two decades were analyzed using the Bibliometrix algorithm in R, revealing a significant increase in research output in this area, evidenced by the substantial growth in the number of published articles and citations received. Additionally, a correlation was observed between scientific production and public policies related to hydrogen, highlighting initiatives in countries such as the United States, China, Germany, Japan, and South Korea, which have been promoting the transition to more sustainable technologies. This study uncovered important trends and guides future innovations in the environmental and transportation sectors, highlightinfg the transition to more sustainable options. The work provided valuable insights into the life cycle of vehicles with various propulsion technologies, emphasizing the evolution and environmental impacts of electric, hybrid, internal combustion, and fuel cell vehicle